2011
DOI: 10.1007/s10103-011-0882-5
|View full text |Cite
|
Sign up to set email alerts
|

Micromorphology and adhesive performance of Er:YAG laser-treated dentin of primary teeth

Abstract: This study evaluated (1) the micromorphology by scanning electron microscopy (SEM) and (2) the adhesive performance by microtensile bond strength (μTBS) of diamond bur-treated dentin compared to Er:YAG laser-treated dentin of human primary teeth. (1) For qualitative SEM evaluation, dentin of 18 second primary molars (n = 3/method) was treated with either diamond bur as a control (group 1a: 40 μm diamond bur only (clinical situation); group 1b: grinding + 40 μm diamond bur) or with Er:YAG laser (group 2a (clini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 24 publications
1
19
0
Order By: Relevance
“…They observed no carbonization or cracks, and the SEM micrographs were similar to those of permanent teeth. Flury et al [37] compared the dentinal morphology of primary teeth using an Er:YAG laser and a diamond bur, and they reported open dentin tubules for all the laser-treated groups. These results were in accordance with our findings; we observed open dentin tubules for both laser groups when compared to the control group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They observed no carbonization or cracks, and the SEM micrographs were similar to those of permanent teeth. Flury et al [37] compared the dentinal morphology of primary teeth using an Er:YAG laser and a diamond bur, and they reported open dentin tubules for all the laser-treated groups. These results were in accordance with our findings; we observed open dentin tubules for both laser groups when compared to the control group.…”
Section: Discussionmentioning
confidence: 99%
“…The same parameters of Er:YAG laser in primary teeth have not been studied yet. However, similar power setting of Er:YAG laser in primary teeth was used in a few studies [12, 13, 37, 38]. Zhang et al [13] reported that laser power of less than 4 W at Er:YAG laser should be used for cavity preparation in primary teeth.…”
Section: Discussionmentioning
confidence: 99%
“…According to the results of the current study, the mean shear bond strength in the groups prepared by laser was slightly higher than the groups prepared by bur, although the difference was not statistically significant and was in agreement with the results of the previous studies. 33,34 This little increase in shear bond strength in groups prepared by laser is probably due to the morphologic properties of the surface after preparation by laser. 35 In the present study, the application of sodium hypochlorite with different concentrations did not show a statistically significant increase in mean shear bond strength compared with the other groups without application of sodium hypochlorite, which was consistent with the results of the study conducted by Gowda et al They reported that using 10% sodium hypochlorite can completely remove the smear layer, and higher concentrations can decrease the application time.…”
Section: Discussionmentioning
confidence: 99%
“…[14][15][16][17][18][19][20][21] Some other results have reported no difference in the bond strength or leakage of adhesive restorations between bur and laser prepared restorative cavities. [22][23][24][25] At different laser parameters, different amount of tooth ablation and thermo-chemical changes occur on tooth surfaces, resulting in different performances from the same adhesives. Laser energy is one of the most important parameters affecting the characteristics of the prepared surface.…”
Section: Introductionmentioning
confidence: 99%